La fille aînée du latin… est restée célibataire trop longtemps - Jean-Michel Eloy (La Bretagne Linguistique, 1998)
If there is a 'French sociolinguistic exception', particularly in the relationship between the French language and the other languages of France, the practical day-to-day realities do not reveal it clearly: the concept of diglossia describes them quite well. After discussing the thesis of the 'French exception' as seen through the prism of language policy, the author examines the concept of 'colinguism' and finally concludes that there is a national linguistic ideology.